Forecasting the Electricity Need for the Household Sector PT. PLN (Persero) Rayon Lhoksukon with Time Series Linear Regression - Ummi Habibah; Muhammad Muhammad; Affitdal Randi (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2022)
Predictions of electricity demand such as connected power and the country's consumption of electrical energy continue to increase every year by population growth in Indonesia. This will cause the number of electricity customers to increase. PLN as a provider of electricity is important to predict long-term electricity demand as the direction of the company's economic policy to meet customer needs. This activity will be reviewed in the electricity distribution area of PT. PLN (PERSERO) Rayon Lhoksukon and its surroundings. Prediction of electricity demand is done through forecasting the number of electricity customers using the time series analysis method with regression from the previous data review from 2016 to 2019. The results show, the form of forecasting , results in the number of electricity customers in 2030 being 6005 customers or an average increase of 2 0.08%/year. The functional relationship between the number of subscribers and connected power is close to a straight line, approached by linear regression, in the form of , resulting in connected power in 2030 being 6927851.4 VA or an average increase of 2.51%/year . Meanwhile , the functional relationship between the number of customers and consumption of electrical energy is close to a straight line, approached by linear regression, in the form of , resulting in electrical energy consumption in 2030 being 67580665.04 kWh or an average increase of 1.15%/year